Pemberdayaan Kewirausahaan Ibu-Ibu PKK melalui Pelatihan Olahan Ikan Laut di Desa Sumurgayam Kecamatan Paciran Kabupaten Lamongan - Hidayati, Novi Itsna; Lidyana, Novita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2022)
Entrepreneurship and entrepreneurship itself is an effort that involves other resources such as natural resources, capital and technology, so as to create wealth and prosperity through job creation, income and products needed by society. Sumurgayam village is located in Paciran District, Lamongan Regency. Most of the inhabitants work as fishermen. The catch from these fishermen is usually only consumed directly by frying or in vegetables. To increase the selling value of sea fish, several alternative processing is needed which can later increase the income of the people in the village. This community service aims to (1) Provide Information, Education and Training to cadets; (2) Providing knowledge and education about the manufacture of processed foods made from marine fish; and (3) Provide knowledge on how to use science and technology media to market products online. The approach methods carried out include an approach with the Village Government in order to synergize village activity programs, socialization and training, direct practice and ongoing mentoring. The results obtained that the enthusiasm of PKK mothers in Sumurgayam Village, Paciran District in participating in training and counseling was very high, so that after attending the training, most of the participants were able to apply the knowledge gained, namely the processing of sea fish with a variety of flavors.